Searching for Sunday : loving, leaving, and finding the Church - Evans, Rachel Held, 1981-2019- (Thomas Nelson Inc, 2015)
"For a generation that has largely said, "count me out," church represents a complicated relationship of both longing and apathy. There's a history there- a past full of confusion and hurt, but a past that often is impossible to abandon. In Searching for Sunday, Rachel Evans exposes her own thorny relationship with the church, articulating the concerns, frustration, and hopes of many of her peers."-- back cover